Identification of BCAR3 by a random search for genes involved in antiestrogen resistance of human breast cancer cells. - van Agthoven, T (1998)
The antiestrogen tamoxifen is important in the treatment of hormone-dependent breast cancer, although development of resistance is inevitable. To unravel the molecular mechanisms of antiestrogen resistance, a search for involved genes was initiated. Retrovirus-mediated insertional mutagenesis was applied to human ZR-75-1 breast cancer cells. Infected cells were subjected to tamoxifen selection and a panel of resistant cell clones was established. Screening for a common integration site resulted in the identification of a novel gene designated BCAR3. Transfer of this locus by cell fusion or transfection of the BCAR3 cDNA to ZR75-1 and MCF-7 cells induces antiestrogen resistance. BCAR3 represents a putative SH2 domain-containing protein and is partly homologous to the cell division cycle protein CDC48.